Typological and chronological variation of burial in Qatar: ʿUbaid to late pre-Islamic (poster) - Cuttler, Richard T.H.; Al Naimi, Faisal A.; Tetlow, Emma A. (Proceedings of the Seminar for Arabian Studies, 2013)
Approximately sixty years of survey and excavation have revealed the presence of extensive burial cairns, particularly in the north of Qatar, indicating that this monument class may number in the tens of thousands. While excavation demonstrates that many of the mounds date between 300 BC and AD 300, more recently the chronology of these monuments has been extended to the fifth millennium BC, suggesting that they reflect mortuary practices over a much longer period than previously thought. As the majority of mounds have been disturbed in antiquity, where possible this paper focuses on undisturbed examples representative of the currently known range of burial types. Where the same burial typology is evidenced from several excavations, representative examples have been cited with a preference for unpublished (and as a result) less accessible literature. These representative examples are used to propose a typology for the future classification of burials in Qatar and to address research priorities that could form the basis of a National Research Framework for the future excavation and study of these monuments.